Incipient speciation driven by hypertrophied lips in Midas cichlid fishes?. Issue 8 (9th March 2017) - Machado‐Schiaffino, Gonzalo; Kautt, Andreas F.; Torres‐Dowdall, Julian; Baumgarten, Lukas; Henning, Frederico; Meyer, Axel
Abstract: Sympatric speciation has been debated in evolutionary biology for decades. Although it has gained in acceptance recently, still only a handful of empirical examples are seen as valid (e.g. crater lake cichlids). In this study, we disentangle the role of hypertrophied lips in the repeated adaptive radiations of Nicaraguan crater lake cichlid fish. We assessed the role of disruptive selection and assortative mating during the early stages of divergence and found a functional trade‐off in feeding behaviour between thick‐ and thin‐lipped ecotypes, suggesting that this trait is a target of disruptive selection. Thick‐lipped fish perform better on nonevasive prey at the cost of a poorer performance on evasive prey. Using enclosures in the wild, we found that thick‐lipped fish perform significantly better in rocky than in sandy habitats. We found almost no mixed pairs during two breeding seasons and hence significant assortative mating. Genetic differentiation between ecotypes seems to be related to the time since colonization, being subtle in L. Masaya (1600 generations ago) and absent in the younger L. Apoyeque (<600 generations ago). Genome‐wide differentiation between ecotypes was higher in the old source lakes than in the young crater lakes. Our results suggest that hypertrophied lips might be promoting incipient sympatric speciation through divergent selection (ecological divergence in feeding performance) and nonrandom mating (assortative mating) in the young Nicaraguan crater lakes. Nonetheless, further manipulative experiments are needed in order to confirm the role of hypertrophied lips as the main cue for assortative mating.